Biomechanical Study of the Vestibular System of the Inner Ear Using a Numerical Method - Santos, Carla F. (2019)
The inner ear has two main parts, the cochlea, dedicated to hearing, and the vestibular system, dedicated to balance. Dizziness and vertigo are the main symptoms related to vestibular disorders, which commonly affects older people. In order to eliminate these symptoms a vestibular rehabilitation is performed; this consists in a range of movements of the head, known as maneuvers, performed by a clinical professional. This procedure does not always work as expected. The aim of this work is to contribute to a better understanding on how the vestibular system works. This knowledge will help in the development of new techniques that will facilitate a more efficient rehabilitation. In order to achieve that goal, a three-dimensional numerical model of the vestibular system, containing the fluids which promote the body balance, was constructed. The vestibular components will be discretized using the finite element method and the fluid flow will be analyzed using the Smoothed Particle Hydrodynamics The results obtained with the numerical model of the semicircular canal built to study the rehabilitation process are presented and compared with other authors. The solution achieved is similar with literature.